Challenges in developing Baitul Maal wat Tamwiil (BMT) in Indonesia using Analytic Network Process (ANP) / Aam S. Rusydiana and Abrista Devi - Rusydiana, Aam S.; Devi, Abrista (Faculty of Business Management, 2013)
This study attempts to identify the dominant factors that has become obstacles in the development of BMT in Indonesia using Analytic Network Process (ANP). The results show that main problems can be divided into four aspects, namely Human Resources, Technical, Legal and Structural, and Market/Communal. The overall problem decomposition shows priorities results, they are: 1) the lack of legal support; 2) the weak of supervision and coaching; 3) the absence of LPS; 4) lack of human resources understanding; and 5) competition. The level of agreement based on Kendall‟s coefficient indicates that the value of Kendall‟s (W) is between 0.592-0.742. The results show that between practitioners and experts relatively dissent in their opinion related to problems and solutions identifying of BMT development in Indonesia.